1995
DOI: 10.1074/jbc.270.2.892
|View full text |Cite
|
Sign up to set email alerts
|

Purified Horseshoe Crab Factor G

Abstract: Horseshoe crab hemocyte lysate responds to (1-->3)-beta-D-glucans, initiating an enzymatic cascade, which culuminates in clot formation. We have purified to homogeneity the serine protease zymogen factor G, which is directly activated by (1-->3)-beta-D-glucans and which initiates the hemolymph clotting cascade. Factor G is a heterodimeric protein composed of two noncovalently associated subunits alpha (72 kDa) and beta (37 kDa). In the presence of (1-->3)-beta-D-glucans such as curdlan and paramylon, factor G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…These observations imply that excess linearized Lystype PG acts as a competitive inhibitor by sequestering Tm-PGRP-SA molecules, thereby impairing the initial activating complex composed of clustered PGRP-SA molecules bound to one linearized PG molecule. Similar observations were reported in the recognition of β-1,3-glucan by Factor G in horseshoe crab, and in the recognition of LPS by the proPO system of crayfish (45,46).…”
Section: Clustering Of Tm-pgrp-sa Is Needed For Activation Of the Lyssupporting
confidence: 73%
“…These observations imply that excess linearized Lystype PG acts as a competitive inhibitor by sequestering Tm-PGRP-SA molecules, thereby impairing the initial activating complex composed of clustered PGRP-SA molecules bound to one linearized PG molecule. Similar observations were reported in the recognition of β-1,3-glucan by Factor G in horseshoe crab, and in the recognition of LPS by the proPO system of crayfish (45,46).…”
Section: Clustering Of Tm-pgrp-sa Is Needed For Activation Of the Lyssupporting
confidence: 73%
“…Interestingly, glucan binding proteins from silkworm, tobacco hornworm, fall webworm, fly, and mealworm are all replaced with other residues, suggesting that these GRPs do not have glucanase enzyme activity. However, other 1,3-␤-Dglucan recognition or binding proteins, such as factor-G of horseshoe crab (33), coelomic cytolytic factor 1 of earthworm (39), LGBP of crayfish (10), and GNBPs of mosquito (38) and silkworm (36), have all conserved Glu residues in the active site as the bacterial glucanase (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins contain a similar domain with those of ␤-1,3-and ␤-1,4-bacterial glucanase (48) and ␤-1,3-glucanase of sea urchin Strongylocentrotus purpuratus (49). It was reported that this region also exists in the GNBPs of B. mori (Bm-GNBP) (36), Drosophila melanogaster (Dm-GNBP) (35), and Hyphantria cunea (Hc-GNBP) (37); putative GNBP of Anopheles gambiae (Ag-GNBP) (38); coagulation factor G of the horseshoe crab Tachypleus tridentatus (Factor-G) (33), LGBP of the crayfish Pacifastacud leniuschlus (10), and Coelomic cytolytic factor 1 of an earthworm (CCF-1) (39). But, as shown in Fig.…”
Section: Identification Of a 13-␤-d-glucan Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…This response is important for the host defense's ability to engulf and kill invading microbes. The granular components include two PAMP-sensitive zymogens, factor C (20) and factor G (21,22). These serine protease zymogens are autocatalytically activated by LPS and ␤-1,3-glucans, respectively.…”
mentioning
confidence: 99%